STRATEGI PENINGKATAN EFEKTIVITAS OPERASIONAL SENTRA KELAUTAN DAN PERIKANAN TERPADU NATUNA: Strategies for Increasing the Operational Effectiveness of the Natuna Integrated Marine and Fisheries Center - Arifnur, Muhammad; Nurani, Tri Wiji; Solihin, Iin (Bogor Agricultural University, 2023)
The Natuna Integrated Maritime and Fisheries Center (IMFC) was established to integrate fish landing, processing, and marketing activities. However, until 2019, the operation of IMFC had not been optimized, hence the objectives of its establishment had not been achieved. This study aims to assess the operational effectiveness of IMFC Natuna and develop strategies for its improvement. The research was carried out by identifying port facilities and capacities that have been built and assessing their operational performance. The strategy for increasing IMFC Natuna's operational activities was prepared using a SWOT analysis. The results show that the facilities at IMFC Natuna have been built completely and are currently in good, clean, and well-maintained condition. IMFC operational performance results from negative gap analysis on fish unloading parameters, namely fish production indicators and ship visits; the parameter of preparation of supplies on ice provision indicator; and marketing parameters on the indicator of the number of fish marketed. The service satisfaction assessment obtained an unsatisfactory rating on the provision of integrated cold storage facilities, provision and marketing services, as well as facilities for fish auctions. Strategies for increasing the operational activities of IMFC Natuna include empowering and improving fishers' skills, making regulations so that trading activities and business activities are centered in IMFC Natuna, inviting investors to develop fisheries investment, and bringing in fishing fleets from outside Natuna. Keywords: Gap, Natuna, operational, IMFC, Strategy.